Influence of work role on transgender's work engagement and social support - Shahzadi, Asma; Atta, Naheed; Rasheed, Ayesha (Institut Agama Islam Negeri Langsa, 2024)
The research aims to find out the level of work engagement and social support among transgenders performing traditional work role and transgender's performing non-traditional work role. Cross sectional and correlational research design were used with purposive sampling of 200 transgenders (traditional work performer n=100 and non-traditional work performer n = 100) from different Non-Government Organizations of Lahore, Pakistan. A series of questionnaire as Utrecht work engagement scale and Multidimensional scale of perceived social support was administered to transgenders after taking consent. Regression and correlation analysis were used to analyse data. Results revealed that work engagement and social support were significantly high in non-traditional work performing transgenders as compared to traditional work performing transgenders. Research conclusion specifies that work engagement predicts social support among transgenders work role. Lastly, inclusion of more researches in this community recommended to make them active and contributing citizens.